A1.3 Phenotyping B-cell may have value as RA diagnostic biomarker for patients with <12 months inflammatory arthritis. (31st January 2014) - Burska, A; Parmar, R; Emery, P; Melado, M; Sacre, S; Ponchel, F
Abstract : Background: Biomarkers for early diagnosis of RA are still needed despite the improvement brought about by the use of the ACR/EUALR-2010 criteria which include the ACPA biomarker. B-cell subset dys-regulation has not been studied in detail in the early RA disease continuum. The aim of this pilot study is to determine whether B-cell subset phenotyping investigating differentiation subset and cell surface expression for TLRs and chemokine receptors can discriminate between patients who clearly are RA from those with other (inflammatory) rheumatic diseases in an early arthritis clinic. Methods: 46 patients with <12 months IA were enrolled; age, CRP, joint counts, symptom duration, RF and ACPA were recorded. 6-8 colour flowcytometry was performed using standard protocols. Results: Using newly developed 2010-RA diagnosis criteria 23 of the 46 patients were diagnosed with RA. Not surprisingly, ACPA positivity was associated with RA (P<0.0001) as part of the criteria, as well as higher CRP (P = 0.004) and swollen joint count (P = 0.003). Differentiation subset analysis showed that naïve B-cells (CD19 + CD27+CD38-) were increased in RA patients (P = 0.028). Furthermore, putative regulatory B-cells (CD19 + CD38+CD24+) were reduced (P = 0.003). More B-cells expressing TLR4 (P = 0.037) were associated with RA but less B-cells expressed CXCR4 (P = 0.012) and CCR6 (P = 0.002). Clustering analysis was used to further investigate pattern of expression of specific groups of markers or phenotypes. Clustering showed 3 groups of patients, one enriched for RA and the other two with mixed RA and non-RA patients (P = 0.088). ACPA positivity was associated with the first group (P = 0.024). Clustering also highlighted IL-6R as a possible marker associated with subgroup-1 (p = 0.001) and ACPA positivity. Conclusion: There are clear B-cell related immunological differences in patients with early RA. We will therefore need to evaluate these biomarkers in early inflammatory patients with a high risk of progression towards RA and establish their value in larger number of patients.